Hubungan Work–Life Balance dan Kepuasan Kerja Dengan Produktivitas Karyawan Milenial - Iim Al Imron (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
Employee productivity among millennials has become a strategic issue in human resource management in the modern era, particularly amid increasing demands for work flexibility and personal life balance. Work–life balance and job satisfaction are regarded as two important factors that potentially influence employee productivity levels. This study aimed to analyze the relationship between work–life balance and job satisfaction with the productivity of millennial employees. The study employed a descriptive analytic design with a correlational approach. A total of 125 millennial employees at Universitas Bhakti Husada Indonesia (UBHI) were selected using a total sampling technique. Data were collected through structured questionnaires and analyzed using the Spearman Rank correlation test. The results showed that there was a significant relationship between work–life balance (p = 0.000) and job satisfaction (p = 0.000) with the productivity of millennial employees. Employees with higher levels of work–life balance and job satisfaction tended to demonstrate better work productivity. This study concludes that improving work–life balance and job satisfaction is a crucial strategy for enhancing the productivity of millennial employees. UBHI is therefore recommended to develop flexible work policies, create a supportive work environment, and implement fair reward systems to optimize the performance of the millennial workforce.